Em busca de uma paternidade envolvida: uma pesquisa na abordagem junguiana - Amaral, Amanda Spínola (2021)
The notions about fatherhood and its roles have changed throughout history, notably because of social changes that began in the 1970s, which led men to perform different roles in the social, family, and individual spheres. This research aims to understand how heterosexual men cohabiting with offspring and a partner envision the exercise of fatherhood in current times. This is an exploratory study with a qualitative design, whose development takes place from a Jungian perspective. Semi-structured individual interviews were carried out with ten adult men, between 33 and 43 years old, who had at least one child, between 2 and 5 years old. The results show that, for the participants, fatherhood is an important transitional moment, which prompts them to assume new roles and responsibilities. Their speeches reveal that, on the one hand, they wish to be more affectionate and involved in the direct care activities given to their children, thus differentiating themselves from their personal fathers, and, on the other hand, they show that this desire does not always translate into changes in their daily practices. The difficulties reported by them are related to establishing boundaries for their children, and to what they call the feminine universe, which encompasses the notion of intimacy in relationships with their children. The wife's professional career, as well as the fact that she earns more than her partner, seem to be related to the amount of responsibility taken by the man in the care of the children. Likewise, the possibility of home office work and the flexibility of working hours are referred by the participants as aspects that favor their involvement in those activities. The symbolic perspective adopted allows to identify the images underlying the speeches and behaviors of the participants, making room to notice the ambiguity that is revealed in a transitioning fatherhood, established through the tension between aspects traditionally attributed to fathers and the commitment to the direct care of their children, associated with the desire to actively participate in their children’s lives and be more affectionate